Wide-band Simultaneous Observations of Pulsars: Disentangling Dispersion Measure and Profile Variations - Hassall, T; Stappers, B; Hessels, J; Kramer, M; Alexov, A; Anderson, K; Coenen, T; Karastergiou, A; Keane, E; Kondratiev, V; Lazaridis, K; Leeuwen, J; et al. (2012)
Dispersion in the interstellar medium is a well known phenomenon that follows a simple relationship, which has been used to predict the time delay of dispersed radio pulses since the late 1960s. We performed wide-band simultaneous observations of four pulsars with LOFAR (at 40-190 MHz), the 76-m Lovell Telescope (at 1400 MHz) and the Effelsberg 100-m Telescope (at 8000 MHz) to test the accuracy of the dispersion law over a broad frequency range. In this paper we present the results of these observations which show that the dispersion law is accurate to better than 1 part in 100000 across our observing band. We use this fact to constrain some of the properties of the ISM along the line-of-sight and use the lack of any aberration or retardation effects to determine upper limits on emission heights in the pulsar magnetosphere. We also discuss the effect of pulse profile evolution on our observations, and the implications that it could have for precision pulsar timing projects such as the detection of gravitational waves with pulsar timing arrays.